KIAA1429 and ALKBH5 Oppositely Influence Aortic Dissection Progression via Regulating the Maturation of Pri-miR-143-3p in an m6A-Dependent Manner - Wang, Peng; Wang, Zhiwei; Zhang, Min; Wu, Qi; Shi, Feng; Yuan, Shun (Frontiers in Cell and Developmental Biology, 2021)
Despite decades of study into aortic dissection (AD), the factors influencing its progression and the deeper regulatory mechanisms remain poorly understood. Nowadays, with the maturity of N6-methyladenosine (m6A) sequence technology, m6A-modification has gradually become a new research hotspot for epigenetic molecular regulation. Especially recently, increasing evidence has revealed that m6A-modification functions as a pivotal post-transcriptional modification to influence the progression of multiple diseases. However, most of the above findings are confined to tumor research, and studies in the cardiovascular system remain almost non-existent. To explore whether m6A-modification also influence AD progression and to elucidate its underlying molecular mechanism of action, we conducted the present study. In this study, we found that KIAA1429 is downregulated while ALKBH5 is upregulated in aortic tissues from AD patients. Furthermore, gain and loss of function studies showed that KIAA1429 and ALKBH5 can oppositely regulate HASMCs proliferation, HAECs apoptosis, and AD progression in AngII-infused mice. Mechanistically, we demonstrated that KIAA1429/ALKBH5-mediated m6A-modifications can regulate the processing of pri-miR-143-3p through interacting with the microprocessor protein DGCR8, thus indirectly regulating the downstream target gene of mature miR-143-3p, DDX6, to perform their biological functions in vitro and in vivo. Our findings have revealed a novel connection between m6A-modification and AD progression and may provide a novel molecular basis for subsequent researchers to searching for novel therapeutic approaches to improve the health of patients struggling with AD.